Pharmacogenetics in Ghana: reviewing the evidence - Kudzi, W.; Adjei, G.O.; Ofori-Adjei, D.; Dodoo, A.N. (My University, 2011)
Different clinical response of different patients to the same medicine has been recognised and documented since the 1950's. Variability in response of individuals to standard doses of drug therapy is important in clinical practice and can lead to therapeutic failures or adverse drug reactions. Pharmacogenetics seeks to identify individual genetic differences (polymorphisms) in drug absorption, metabolism, distribution and excretion that can affect the activity of a particular drug with the view of improving efficacy and reducing toxicity. Although knowledge of pharmacogenetics is being translated into clinical practice in the developed world, its applicability in the developing countries is low. Several factors account for this including the fact that there is very little pharmacogenetic information available in many indigenous African populations including Ghanaians. A number of genes including Cytochrome P450 (CYP) 2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, MDR1 and TPMT have been genotyped in the Ghanaian population since the completion of the Human genome project. There is however, an urgent need to increase pharmacogenetic research in Ghana to increase availability of data. Introducing Pharmacogenetics into the curriculum of Medical and Pharmacy training institutions will influence translating knowledge of pharmacogenetics into clinical practice. This will also equip health professionals with the skill to integrate genetic information into public health decision making.
Keywords: EMTREE medical terms: article; gene frequency; genetics; genotyping technique; Ghana; human; Negro; pharmacogenetics; single nucleotide polymorphism; MeSH: African Continental Ancestry Group; Gene Frequency; Genotyping Techniques; Ghana; Humans; Pharmacogenetics; Polymorphism, Single Nucleotide